2015
DOI: 10.3329/bioethics.v6i2.25739
|View full text |Cite
|
Sign up to set email alerts
|

Medical Ethics and Medical Professionalism in Low and Middle Income (LAMIC) Countries: Challenges and Implications.

Abstract: This article examines the (bio) ethical and professionalism issues that may arise in the context of medical practice in low and middle income countries (LAMIC), and the challenges this poses for medical regulatory bodies in the regions, in upholding ethics in professional practice. A quadrangle of source of the problems given rise to the breach of ethics in medical practice is identified, and suggested steps, based on ethical principles and concept, is proposed towards the resolution of the problems presented.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…At both universities, ethics was not examinable as a core subject, but was examined within the other core disciplines. [4] There were no lecturers identified as having been trained specifically in clinical/medical ethics by either the administrators, the lecturers or the medical students, but both the medical students and lecturers indicated that those teaching had some interest in ethics.…”
Section: The University Approved Curricula For Medical Studentsmentioning
confidence: 99%
See 2 more Smart Citations
“…At both universities, ethics was not examinable as a core subject, but was examined within the other core disciplines. [4] There were no lecturers identified as having been trained specifically in clinical/medical ethics by either the administrators, the lecturers or the medical students, but both the medical students and lecturers indicated that those teaching had some interest in ethics.…”
Section: The University Approved Curricula For Medical Studentsmentioning
confidence: 99%
“…The brain drain has caused human personnel in the healthcare sector to be outnumbered by the rising volume of patients [4,18]. The uneven doctor to patient ratio overburdens lecturers, which can account for the lack of role models and attention given to teaching in medical schools in resource-limited settings.…”
Section: Lack Of Attention In Teaching Ethics and Role Modellingmentioning
confidence: 99%
See 1 more Smart Citation